Distribution and source apportionment studies of heavy metals in soil of cotton/wheat fields - Rafique, Nazia; Tariq, Saadia R. (Environmental monitoring and assessment, 2016)
Heavy metals enriched agricultural soils have been the subject of great concern because these metals have potential to be transferred to the soil solution and afterward accumulated in food chain. To study the trace metal persistence in crop soil, 90 representative soil samples were collected and analyzed for heavy metal (As, Cd, Cu, Fe, Mn, Ni, Pb, and Zn) and anions (chloride, nitrates, phosphates and sulfates). Cluster and factor analysis techniques were used for the source identification of these excessive heavy metal levels and ecological risk was determined with potential ecological risk assessment. The degree of enrichment of eight studied heavy metals in comparison with the corresponding background levels decreased in order: Cd > Pb > Fe > Ni > Mn > As > Cu ~ Zn. Arsenic and cadmium exhibited 1.30- and 1.64-fold exceeded levels than threshold limits set by National environment quality standards, respectively. Cd in cotton field’s soil may lead to higher potential risk than other heavy metals. On overall basis, the cumulative mean potential ecological risk for the district (207.75) corresponded to moderate risk level with higher contributions from As and Pb especially from Cd. Cadmium formed strong positive correlation with phosphate content of soil at p < 0.01. Cluster analysis indicated that Cluster 1 (extremely polluted) probably originated from anthropogenic inputs of phosphate fertilizer and past usage of arsenical pesticides.